Russian animalier art of the New Age. On the problem of genre specifics - Portnova, Irina Vasilievna (University of the Free State, 2017)
The article examines the peculiarities of Russian animalier art. The work’s relevance is that it brings to light the new ontological and morphological status of animalistic art that has to do with the composition of the modernera world picture from the 18th to the first half of the 20th centuries, which differs in many respects from its mediaeval counterpart. The article is aimed at revealing the peculiarities of animalier art in the context of the era and existing genres, understanding its specific nature as determined by the animal model and the perception of it that implies the evaluation of objective and subjective factors in an image. In addition, the article looks at the peculiarities of an animalier artist’s working method as he or she deals with a mobile model not prone to posing, his or her priorities of plot and theme in depicting animals, and the significance of animalier art in general. The article shows that the major initial principle for artists involved in animal depiction was the imitation of nature. This eventually led to the formation of a separate genre, namely animalier art, with a set of distinctive features of its own. The article takes the historical-problematic method as its major approach, implying the articulation of issues specific to the animalistic genre as well as historical-artistic issues, which makes it possible to give a valuation to the artistic aspects of Russian animalier art as a distinctive, original phenomenon in history. The au thor notes the significance of the animalistic genre, a genre from the academic environment and one which has had a major role as a school of professional excellence. Despite the length of time that animalier art has been around, it has managed to preserve its “genre memory” and the unity of its morphological characteristics in various types of art. It made it past the 20th Century and is still around today. The material covered in the paper is of value for art history, as it enriches national art with new research findings and little-known facts, for pedagogics, and also in the broader, philosophical sense, as it raises issues of a moral nature (the interrelationship between man and animals).
Keywords: Genre; Animalier art; Animalistic art; Animal; Science; Concept; Era; Epoch; Kind; Type; School; Character; Sculpture; Graphic art; Graphics; Painting; Pictorial art; Image; Figure